2021
DOI: 10.1021/acs.jpclett.1c03045
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Metallic Phase of a Bilayer Blue Phosphorene Induced by Interlayer Bonding and Intralayer Charge Redistributions

Abstract: We have carried out diffusion Monte Carlo calculations for an A1B–1-stacked bilayer blue phosphorene to find that it undergoes a semiconductor–metal transition as the interlayer distance decreases. While the most stable bilayer structure is a semiconducting one with two monolayers coupled through a weak van der Waals interaction, the metallic bilayer at a shorter interlayer distance is found to be only metastable. This is in contrast to a recent theoretical prediction based on a random phase approximation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This is important to note, as two high-precision methods for layered structures yield different results, as shown in a recent publication on blue phosphorene bilayers. 46 Given the discrepancy between different levels of theory and to confirm the reliability of our results, we performed additional computations at the ACFDT-RPA level based on PBE0 orbitals for three different systems: the lowest energy forms of group I and II (A −1 A′ −1 and A′ −1 B 1 ), and A′ 1 B′ −1 of group III. As shown in Table S1, † the trend of the relative energies between the three systems matches perfectly with those obtained with RPA and PBE orbitals, confirming that the lowest-lying energy form belongs to group I instead of A′ 1 B′ −1 of group III, as indicated by SCAN + rVV10.…”
Section: Energetics and Stabilitymentioning
confidence: 74%
“…This is important to note, as two high-precision methods for layered structures yield different results, as shown in a recent publication on blue phosphorene bilayers. 46 Given the discrepancy between different levels of theory and to confirm the reliability of our results, we performed additional computations at the ACFDT-RPA level based on PBE0 orbitals for three different systems: the lowest energy forms of group I and II (A −1 A′ −1 and A′ −1 B 1 ), and A′ 1 B′ −1 of group III. As shown in Table S1, † the trend of the relative energies between the three systems matches perfectly with those obtained with RPA and PBE orbitals, confirming that the lowest-lying energy form belongs to group I instead of A′ 1 B′ −1 of group III, as indicated by SCAN + rVV10.…”
Section: Energetics and Stabilitymentioning
confidence: 74%
“…Our tests show that the relative stabilities of the metallic and semiconducting phases depend on the used func-tionals (see the ESI †) in agreement with the work in ref. 28. However, when taking temperature effects into account, we find that the semiconducting phase will automatically transform into the metallic phase no matter what functionals are used, as demonstrated by our molecular dynamical simulations at 300 K (see the ESI †), indicating that the metallic phase is likely to be obtained if bilayer blue-P can be made.…”
mentioning
confidence: 72%
“…However, after studying diverse stacking modes of bilayer blue-P, J. Arcudia et al reported that the most stable stacking configuration shows metallic behavior with the A 1 B −1 arrangement. 27 Another work by J. Ahn et al reported that the most stable bilayer blue-P is semiconducting with a much larger layer distance 28 by considering the many-body effects. Our tests show that the relative stabilities of the metallic and semiconducting phases depend on the used func-tionals (see the ESI †) in agreement with the work in ref.…”
mentioning
confidence: 99%
“…Among layered materials, phosphorene is a promising candidate due to rich geometric structures that is leading to various polymorphs and polytypes while having none of the obstacles exhibited by other two-dimensional materials. Several structurally different two-dimensional polymorphs of phosphorus namely, α-P, β-P, γ-P, δ-P, ε-P, τ-P, η-P, θ-P, σ-P, ϕ-P, tricycle-type red phosphorene (R-P), square-octagon phosphorene (O–P) and hexagonal-star phosphorene (H–P) have been investigated using first principle methods. Most of these two-dimensional polymorphic materials are semiconductors with a band gap in the range of 0.4 to 2.1 eV. , We recall that α-P and β-P have been prepared experimentally, while other allotropes have not yet been synthesized . According to the polytypism definition, the individual phosphorene allotropes can be coupled through noncovalent interactions leading to bi/tri/few layer phases up to the bulk material .…”
Section: Introductionmentioning
confidence: 99%